Was Mesopithecus a seed eating colobine? Assessment of cracking, grinding and shearing ability using dental topography. Issue 112 (November 2017) - Thiery, Ghislain; Gillet, Geoffrey; Lazzari, Vincent; Merceron, Gildas; Guy, Franck
Abstract: Extant colobine monkeys have been historically described as specialized folivores. However, reports on both their behavior and dental metrics tend to ascribe a more varied diet to them. In particular, several species, such as Pygathrix nemaeus and Rhinopithecus roxellana, are dedicated seasonal seed eaters. They use the lophs on their postcanine teeth to crack open the hard endocarp that protects some seeds. This raises the question of whether the bilophodont occlusal pattern of colobine monkeys first evolved as an adaptation to folivory or sclerocarpic foraging. Here, we assess the sclerocarpic foraging ability of the oldest European fossil colobine monkey, Mesopithecus . We use computed microtomograpy to investigate the three-dimensional (3D) dental topography and enamel thickness of upper second molars ascribed to the late Miocene species Mesopithecus pentelicus from Pikermi, Greece. We compare M. pentelicus to a sample of extant Old World monkeys encompassing a wide range of diets. Furthermore, we combine classic dietary categories such as folivory with alternative categories that score the ability to crack, grind and shear mechanically challenging food. The 3D dental topography of M. pentelicus predicts an ability to crack and grind hard foods such as seeds. This is consistent with previous results obtained from dental microwear analysis. However, its relatively thin enamel groups M. pentelicus with other folivorous cercopithecids. We interpret this as a morphological trade-off between the necessity to avoid tooth failure resulting from hard food consumption and the need to process a high amount of leafy material. Our study demonstrates that categories evaluating the cracking, grinding or shearing ability, traditional dietary categories, and dental topography combine well to make a powerful tool for the investigation of diet in extant and extinct primates.